Agriculture Adaptation to Climate Change in Brunei Darussalam: A Step towards Food Security. (March 2015) - Shams, Shahriar; Shafiuddin, KBM Hj; Sultan, Asmaal Muizz Sallehhin Bin Hj Mohammad; Juani, Rozeana Binti Hj Md.
Globally, climate change is a reality and adaptation to it is now a necessity. It is evident from the Brunei meteorological data analysis that over the last 27 years, the mean annual rainfall has increased by 675 mm during 1985–2012. The mean annual temperature has also increased by 0.794°C during the last 30 years from 1978 to 2008. The standard of living is increasing with the advancement of new technologies and thus increasing the lifespan of individuals. The demand for food production will also increase and Brunei Darussalam relies heavily on import of various food grains, particularly rice having a self-sufficiency rate of only 5.06 per cent. The impact of increased demand for food production will be felt significantly in the agricultural sector. The study looks at the existing agricultural practice, the impact of climate change on agriculture and identifies the training needed for the farmers or agricultural workers to cope with theadverse impact of climate change. A case study was carried out to find the challenges the farmers are likely to face because of the climate change. It has been observed from the field survey that 76 per cent of the respondents involved in farming lack farming skills and experience especially those who are below the age of 30 while only a handful (3 per cent) of them have farming experience. The study reveals that agriculture activities require modification in order to cope with the climate change. A capacity-building process for agricultural adaption for Brunei Darussalam is proposed.